BUILDING A WEBSITE APPLICATION SAVER FAMILY SUPERMARKETS USING CONTENT MANAGEMENT SYSTEMS (CMS) PHPWEBSITE AND BECOME THE ADMINISTRATOR - Azhari Azhari; Linda Wahyu Widianti., SKom, MMSI (Jurnal Sistem Informasi, 2005)
Nowadays the use of Internet services as a means to obtain information more widelyused. This is because the internet has a very wide range. Internet is ideal when used as ameans of delivering information or promotion of an organization or company, to offergoods or services to consumers.As one of the supermarkets are quite developed nowadays, Supermarkets Save Family inneed of a media campaign and information more effectively and efficiently for itscustomers. Therefore, Save the Family Self-Service website making is intended tofacilitate customers to obtain information about various products sold in this supermarket.To build this website, the author uses an application content management system (CMS)called phpWebSite with version 0.8.3, built a Web Technology Group, who came fromAppalachian State University in the United States. And with the help of some supportingsoftware.For the writer, the essence of the making of this website is located on how to build awebsite (whether it be commercial, social and individual) are attractive and easilymanaged.This research aims to encourage students and student Jakara STMIK STI & K inparticular, to develop their imagination and their creativity in the world of web designand readers in general, to participate in advancing the world of web design in Indonesia.